1997
DOI: 10.1539/joh.39.205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intratracheally Administered Indium Phosphide on Male Fischer 344 Rats

Abstract: Effects of Intratracheally Administered Indium Phosphide on Male Fischer 344 Rats: Takamoto Uemura, et al. Department of Preventive Medicine and Public Health, School of Medicine, Keio University—Objective—To examine the effects of intratracheally administered indium phosphide (InP) and distribution of indium on male Fischer 344 rats. Materials and methods—Rats were intratracheally given 0, 1, 10 or 100 mg/kg of InP with a mean diameter of 0.8pm and observed for 1 and 7 days. The bronchoalveolar lavage fluid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…It is well known that the inhalation of hardly soluble hazardous particles, such as crystalline silica, asbestos, and so on, induces pneumoconiosis. In animal experiments, intra-tracheal instillation of indium compounds induces pneumonitis, proliferation of fibrous tissues, pulmonary fibrosis, and other lung diseases [3][4][5][6] . The results of our study are consistent with these information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the inhalation of hardly soluble hazardous particles, such as crystalline silica, asbestos, and so on, induces pneumoconiosis. In animal experiments, intra-tracheal instillation of indium compounds induces pneumonitis, proliferation of fibrous tissues, pulmonary fibrosis, and other lung diseases [3][4][5][6] . The results of our study are consistent with these information.…”
Section: Discussionmentioning
confidence: 99%
“…Until the early 1990's, there was little information on the toxic effects of indium on humans or animals. In the mid 1990's, intra-tracheal instillation studies of particles of compound semiconductors such as indium phosphide, indium arsenide and indium trichloride revealed that metal compounds containing indium had a strong potential to induce severe lung damage [2][3][4][5][6] . In 2003, Homma et al 7) disclosed a case of interstitial pneumonia in a 27-yr-old male worker engaged in the wet surface polishing process of indium-tin oxide (ITO) target plates, high-density plates made of very hard ceramics composed of indium oxide and tin oxide, which are used to laminate transparent electroconductive thin-film on flat displays and solar cells.…”
mentioning
confidence: 99%
“…Due to the increasing production of ITO, the potential health hazards of occupational or environmental exposure to this material have began to cause great concern. Since the mid 1990's, data have become available indicating that indium compounds can be toxic to animals [2][3][4][5][6][7][8][9][10][11][12] , although there is little information regarding the adverse health effects for workers exposed to indium compounds. In 2003, the first case of interstitial pneumonia caused by occupational exposure to ITO was reported 13) .…”
mentioning
confidence: 99%
“…From the mid-1990s, animal experiments have shown that the inhalation or intratracheal instillation of In compounds causes severe lung inflammation [1][2][3][4][5][6][7] and mild adverse reproductive effects [8][9][10] . Although the health effects of In on workers' respiratory and reproductive systems have been unclear to date, assessing the exposure-effect relationships in Inexposed workers is a serious concern, but no information is available on the exposure-effect relationships in workers.…”
mentioning
confidence: 99%